Nuevos datos sobre la fauna albiense de Traiguera (Castellón) - Calzada, S.; Reig, J.M. (Cuadernos de Geología Ibérica, 1993)
The Albian outcrop of Traiguera (Prov. Castellón, NE Spain), was studied by Canerot & Collignon (1981). They described Ammonites, Bivalves and Gastropods. Here new paleontological data about Scleractinia and other Gasteropoda are repported. This fauna comes from Middle Albian beds. Two genera of ScLeractinia añil te seven species of Oastropods are described. The genus Oonia reaches an Albian age. The synonymy of Helicacantizus octavius is pointed out. This species has a large distribution in the Tethyan Albian.
Keywords: Palaeontology Scleractinia Gastropoda Cretaceous NE of Spain